2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333962
|View full text |Cite
|
Sign up to set email alerts
|

Digital thermal monitoring (DTM) of vascular reactivity closely correlates with doppler flow velocity

Abstract: The noninvasive measurement of peripheral vascular reactivity, as an indicator of vascular function, provides a valuable tool for cardiovascular screening of at-risk populations. Practical and economical considerations demand that such a test be low-cost and simple to use. To this end, it is advantageous to substitute digital thermal monitoring (DTM) for the more costly and complex Doppler system commonly used for this measurement. A signal processing model was developed to establish the basis for the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…During the cuff occlusion period, fingertip temperature in the right hand decreased because of the absence of warm circulating blood. When the cuff was released after the 5-minute occlusion, hyperemic blood flow to the forearm and hand was restored, and this resulted in a “temperature rebound” in the fingertip that is directly related to the subject's hyperemic blood flow response, endothelial function, and vascular reactivity [21, 22]. Using the recorded fingertip temperatures, the ambient temperature of the testing room, the observed slope of temperature decline, and a multivariate bioheat formula, the VENDYS software calculated and plotted a zero reactivity curve (ZRC).…”
Section: Methodsmentioning
confidence: 99%
“…During the cuff occlusion period, fingertip temperature in the right hand decreased because of the absence of warm circulating blood. When the cuff was released after the 5-minute occlusion, hyperemic blood flow to the forearm and hand was restored, and this resulted in a “temperature rebound” in the fingertip that is directly related to the subject's hyperemic blood flow response, endothelial function, and vascular reactivity [21, 22]. Using the recorded fingertip temperatures, the ambient temperature of the testing room, the observed slope of temperature decline, and a multivariate bioheat formula, the VENDYS software calculated and plotted a zero reactivity curve (ZRC).…”
Section: Methodsmentioning
confidence: 99%
“…An automated device that controls for systemic sympathetic effects by utilizing data from the non-occlusion finger allows for calculation of the adjusted temperature rebound (aTR). 72 This response has been shown to be abnormal in subjects with various risk factors including diabetes, insulin-resistance and CAD. 73 It has also been shown to be related to the presence of myocardial perfusion defects and obstructive CAD as detected by nuclear scintigraphy and computed tomography coronary angiography respectively.…”
Section: Novel Conceptsmentioning
confidence: 98%
“…While FMD is a non-invasive measurement of vascular reactivity and endothelial-dependent vasomotion 6) , this technique is dependent on technical expertise and expensive ultrasound equipment, thereby restricting it to a vascular research laboratory and therefore being of limited clinical utility in the perioperative setting. DTM, a novel non-invasive technique, utilizing the principle of reactive hyperemia, has also been shown to correlate with Doppler flow velocity 19) , a parameter used in the BART technique. Recent studies investigating DTM showed that impaired vascular reactivity correlated with the extent of myocardial perfusion defect 20) and was found in patients with metabolic syndrome and diabetes mellitus 21) ; however, these lat- compared to their cohorts without obesity.…”
Section: Dtm and Comorbiditiesmentioning
confidence: 99%